PENGEMBANGAN BUKU PINTU AJAIB SEBAGAI MEDIA LAYANAN BIMBINGAN KONSELING PADA SISWA KELAS 6 SEKOLAH DASAR - Qothrun Nada; Nugraha Permana Putra (Jurnal Tunas Pendidikan, 2023)
The study Development of â€œBuku Pintu Ajaibâ€ as A Medium in Guidance and Counseling Service for Elementary School 6th Graders developed a medium for the implementation of Guidance and Counseling. This study aims to determine the development of the "Buku Pintu Ajaib" as a medium for Guidance and Counseling services for 6th grade elementary school students and to determine the feasibility of the "Buku Pintu Ajaib" as a medium for Guidance and Counseling services for 6th grade elementary school students. This research is a Research and Development study following an adaptation of ADDIE research and development study procedures, which is limited to the validation stage. These were conducted by doing performance analysis, needs analysis, product development design, product development manufacturing, and product feasibility validation. The data were collected from questionnaires. From the material and medium feasibility validation conducted by Material Expert, Medium Expert, and Class Teacher, it can be said that â€œBuku Pintu Ajaibâ€ medium is appropriate to be applied, with required revisions, as a medium in the informational and personal services of Guidance and Counseling for elementary school 6th graders.